Molecular signature for senile and complicated cataracts derived from analysis of sumoylation enzymes and their substrates in human cataract lenses. Issue 10 (22nd August 2020) - Liu, Fang‐Yuan; Fu, Jia‐Ling; Wang, Ling; Nie, Qian; Luo, Zhongwen; Hou, Min; Yang, Yuan; Gong, Xiao‐Dong; Wang, Yan; Xiao, Yuan; Xiang, Jiawen; Hu, Xuebin; et al.
Abstract: Sumoylation is one of the key regulatory mechanisms in eukaryotes. Our previous studies reveal that sumoylation plays indispensable roles during lens differentiation (Yan et al. 2010. Proc Natl Acad Sci USA . 107:21034–21039; Gong et al. 2014. Proc Natl Acad Sci USA . 111:5574–5579). Whether sumoylation is implicated in cataractogenesis, a disease largely derived from aging, remains elusive. In the present study, we have examined the changing patterns of the sumoylation ligases and de‐sumoylation enzymes (SENPs) and their substrates including Pax6 and other proteins in cataractous lenses of different age groups from 50 to 90 years old. It is found that compared with normal lenses, sumoylation ligases 1 and 3, de‐sumoylation enzymes SENP3/7/8, and p46 Pax6 are clearly increased. In contrast, Ubc9 is significantly decreased. Among different cataract patients from 50s to 70s, male patients express more sumoylation enzymes and p46 Pax6. Ubc9 and SENP6 display age‐dependent increase. The p46 Pax6 displays age‐dependent decrease in normal lens, remains relatively stable in senile cataracts but becomes di‐sumoylated in complicated cataracts. In contrast, sumoylation of p32 Pax6 is observed in senile cataracts and increases its stability. Treatment of rat lenses with oxidative stress increases Pax6 expression without sumoylation but promotes apoptosis. Thus, our results show that the changing patterns in Ubc9, SENP6, and Pax6 levels can act as molecular markers for senile cataract and the di‐sumoylated p46 Pax6 for complicated cataract. Together, our results reveal the presence of molecular signature for both senile and complicated cataracts. Moreover, our study indicates that sumoylation is implicated in control of aging and cataractogenesis. Abstract : The molecular signatures for both senile cataract and complicated cataract. Upregulation of sumoylation ligases Ubc9 and PIAS1, and de‐sumoylation enzyme SENP6, and SUMO1 conjugation of p32 Pax6 are molecular markers for senile cataract. Di‐sumoylation of p46 Pax6 is the molecular marker for complicated cataract.